China and Cybersecurity: Espionage, Strategy, and Politics in the Digital Domain - Patiño Orozco, Germán Alejandro (México y la Cuenca del Pacífico, 2019)
Resumen Reseña del libro: China and Cybersecurity: Espionage, Strategy, and Politics in the Digital Domain. Jon R. Lindsay, Tai Ming Cheung y Derek S. Reveron (eds.), Oxford University Press, Nueva York, 2015.